THE DETERMINANTS OF BANK CREDIT GROWTH AND CREDIT AGGREGATE BEHAVIOR DURING ALTERNATE BUSINESS CYCLES IN SOUTH AFRICA - Chakanyuka, Dr. Goodman (Journal of Accounting, 2016)
Purpose: The purpose of this study was to Analyze of the Relationship between Business Cycles and Bank Credit Extension: Evidence from South Africa. The study sought establish the determinants of bank credit growth in South Africa and how the different credit aggregates behave during alternate business cycles Methodology: This study adopted qualitative and quantitative research. The qualitative research involves structured interviews with influential or well informed people on the subject matter. The study is used to understand the key determinants of bank credit in South Africa and to appreciate how each of the credit aggregates behaves during alternate business cycles. The qualitative results are used to formulate questions of the structured survey questionnaire. The ANOVA and Pearman's product correlation analysis techniques are used to assess relationship between variables. Results: Results revealed that, key determinants of commercial bank credit in South Africa as economic growth, collateral value, bank competition, money supply, deposit liabilities, capital requirements, bank lending rates and inflation. The quantitative results show that there is direct and positive relationship between bank lending behaviour and credit aggregates namely economic growth, collateral value, bank competition and money supply. Unique contribution to theory, practice and policy: It proposes practical policy prescriptions to address challenges currently facing South Africa. The other major contribution of this study is that it shall open new avenues for further research on determinants of bank credit growth in South Africa and how the different credit aggregates behave during alternate business cycles.